MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN ISLAM BERBASIS ENTREPRENEURSHIP - Suwantoro Suwantoro (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
The management process of good education and systematic by using management service as well as supported by the leadership implementation of headmaster as the man power in an education institution in good education grade level by sthrengthen the aspec of institution finances through investment of soul, attitude and entrepreneurship charac-teristic which implemented in the leadership process of headmaster. To manage and lead education institution is complex thing, the complexity is not only related with quick change, but aslo caused by the development of the school organization internal expectations for the coordination of the education that have more quality and be able to give high satisfaction for entire education consumer, so that the implementation of entrepreneurship in the process to manage and lead the school institution as its basic hopefully could answer the problem and the able to create expectations in the internal adn external of school organization.Keywords: Leadership, Islamic Education, Entrepreneurship